PENGARUH JENIS ZAT FIKSASI TERHADAP KUALITAS HASIL PEWARNAAN PADA BATIK KULIT KAYU JOMOK MENGGUNAKAN KOMBINASI ZAT WARNA JAMBAL, TEGERAN DAN TINGI - Adiningtyas, Ferina Suci (Akademi Kesejahteraan Sosial AKK Yogyakarta, 2024)
This study aims to determine the quality of the coloring results on jomok bark batik using natural dyes (a combination of jambal, tegeran and tingi) without fixation, fixation with alum, fixation with calcium oxide, fixation with tunjung and the influence of the type of fixation agent on the quality of the coloring results on batik Jomok bark uses a combination of jambal, tengeran and tingi dyes. This research is an experimental research with an AxB factorial design. The results of the research on the quality of the coloring results on Jomok bark batik using natural dyes without fixation were a value of 4 in the good category, the quality of the coloring results on Jomok bark batik using natural dyes with alum fixation was a value of 4-5 in the good category, the quality of the coloring results in Jomok bark batik using natural dyes with calcium oxide fixation is a score of 4-5 in the good category, the quality of the coloring results in Jomok bark batik using natural dyes with tunjung fixation is a score of 4-5 in the good category, the type of fixation agent indicates the presence of influence on the quality of jomok bark batik coloring with the best color results with tunjung fixation.